Effect of n-Butanol Blending with a Blend of Diesel and Biodiesel on Performance and Exhaust Emissions of a Diesel Engine - Altun, Sehmus; Oner, Cengiz; Yasar, Fevzi; Adin, Hamit (Amer Chemical Soc, 2011)
Experimental work was conducted to evaluate the effect of using n-butanol (normal butanol) in conventional diesel fuel-biodiesel blends on the engine performance and exhaust emissions of a single cylinder direct injection compression ignition engine with the engine working at a constant engine speed and at different three engine loads. A blend of biodiesel and diesel fuel known as B20 (20% biodiesel and 80% diesel in volume) was prepared, and then n-butanol was added to B20 at a volume percent of 10% and 20% (denoted as B20Bu10 and B20Bu20, respectively). Fuel consumption; regulated exhaust emissions such as nitrogen oxides, carbon monoxide, and total unburned hydrocarbons; and smoke opacity were measured. The brake specific fuel consumption of fuel blends was found to be higher when compared to that of conventional diesel fuel. On the other hand, the addition of n-butanol to the B20 fuel blend caused a slight increase in the brake specific fuel consumption and brake thermal efficiency in comparison to the B20 fuel blend. For exhaust emissions, carbon monoxide (CO) and hydrocarbon (HCs) emissions decreased, and NO(x) remained almost unchanged at low engine loads, while it decreased at high engine loads. Fuel blends also resulted in a sharp reduction of smoke opacity in the whole range of engine tests.
Keywords: Fuel Blends; Oil